Critical Discourse Analysis of Pantun in Elementary School Textbook - Indra Nugrahayu Taufik; Dewi Siti Solihah (Badan Pengembangan dan Pembinaan Bahasa, 2022)
The purpose of this study is to explain the use of pantun in textbooks in elementary schools, especially the description of the use of types of rhymes, errors in the number of syllables, distribution of pantun types based on age/user, distribution of pantun types based on content, distribution of thematic pantun, pantun distribution based on integrativeness, distribution pantun based on cross-curriculum integration. This research is classified as Critical Discourse Analysis which is part of qualitative research so it uses actual, objective, and systematic explanations. The research was conducted by analyzing and interpreting the pantun contained in the text of elementary school textbooks, both those used by teachers and books used by students. Critical discourse analysis is seen from the perspective of the author. This research provides a more concrete picture of the involvement of textbooks in the preservation of pantun as an Indonesian cultural heritage. In this study, positive results were shown, the existence of pantun in textbooks had created expressive spaces for students. AbstrakTujuan penelitian ini untuk menjelaskan penggunaan pantun dalam buku pelajaran di sekolah dasar khususnya uraian penggunaan jenis rima, penggunaan jumlah suku kata, pembagian jenis pantun berdasarkan usia/pengguna, pembagian jenis pantun berdasarkan isi, pembagian pantun tematik, pembagian pantun berdasarkan keterpaduan, pembagian pantun berdasarkan integrasi lintas kurikulum. Penelitian ini tergolong dalam penelitian Analisis Wacana Kritis yang merupakan bagian dari penelitian kualitatif sehingga menggunakan penjelasan yang aktual, objektif, dan sistematis. Penelitian dilakukan dengan menganalisis dan menginterpretasikan pantun yang terdapat dalam teks buku pelajaran sekolah dasar, baik yang digunakan oleh guru maupun buku yang digunakan oleh siswa. Analisis wacana kritis dilihat dari sudut pandang pengarang. Penelitian ini memberikan gambaran yang lebih konkret tentang keterlibatan buku ajar dalam pelestarian pantun sebagai warisan budaya Indonesia. Dalam penelitian ini ditunjukkan hasil yang positif, keberadaan pantun dalam buku pelajaran telah menciptakan ruang ekspresif bagi siswa.